2017
DOI: 10.3791/55033
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-based Regulation of Picornavirus Tropism

Abstract: Cell-specific restriction of viral replication without concomitant attenuation can benefit vaccine development, gene therapy, oncolytic virotherapy, and understanding the biological properties of viruses. There are several mechanisms for regulating viral tropism, however they tend to be virus class specific and many result in virus attenuation. Additionally, many viruses, including picornaviruses, exhibit size constraints that do not allow for incorporation of large amounts of foreign genetic material required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Picornavirus toxicity can be subdued through miRNA-mediated detargeting to prevent viral replication in off-target tissues, which is a well-studied technique. 1 , 13 , 50 , 51 , 52 This technique has worked very effectively for improving the safety profile of Mengovirus. The dual-detargeted Mengovirus, vMC 24 NC, showed potent therapeutic efficacy in a syngeneic plasmacytoma MPC-11 model without significant neuro- and cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Picornavirus toxicity can be subdued through miRNA-mediated detargeting to prevent viral replication in off-target tissues, which is a well-studied technique. 1 , 13 , 50 , 51 , 52 This technique has worked very effectively for improving the safety profile of Mengovirus. The dual-detargeted Mengovirus, vMC 24 NC, showed potent therapeutic efficacy in a syngeneic plasmacytoma MPC-11 model without significant neuro- and cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this, miRNA-detargeting has become an effective method for selectively controlling the tissue tropism and toxicity of a variety of RNA and DNA viruses. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Our laboratory has previously demonstrated that the miRNA-detargeting strategy can be used to moderate the neuro- and cardiotoxicities associated with a poly(C) truncated oncolytic Mengovirus, vMC 24 , while retaining the virus’ ability to replicate in a wide range of murine and human cancer cells. 12 This virus, vMC 24 NC, generated by inserting neuron- and cardiac/muscle-specific miRNA targets into the 5′ and 3′ non-coding regions (NCRs) of the viral genome, showed excellent therapeutic efficacy against a syngeneic murine plasmacytoma (MPC-11) model without significant virus-mediated toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-RNA (miRNA) is evolving as a regulator of vector tropism, 120 , 121 which is in contrast to the initial descriptions of RNA viruses where vector tropism could not be controlled through transcriptional targeting. This was evident in the case of coxsackievirus type A21, which causes off-target severe, often fatal myositis.…”
Section: Immunomodulation At the Tumor Microenvironmentmentioning
confidence: 96%
“…Because of their positive-sense RNA genomes, oncolytic picornaviruses are especially suitable for another form of post-viral entry replication control, which hijacks the miRNA gene expression control network to regulate viral permissivity. miRNA-targeting elements inserted within the viral genome target picornaviruses for degradation in healthy tissues expressing the cognate miRNA, while replication occurs unencumbered in neoplastic tissues where the cognate miRNA is not expressed [ 116 ]. This approach was shown to reliably eliminate fatal CAV21-associated myotoxicity in OV mouse models, both in the infectious RNA and viral particle formulation [ 117 119 ].…”
Section: Applicationsmentioning
confidence: 99%